The oomycete Lagenisma coscinodisci hijacks host alkaloid synthesis during infection of a marine diatom - Marine Vallet (Nature Portfolio, 2019)
Flagellated oomycetes frequently infect unicellular algae, thus limiting their proliferation. Here, the authors show that an oomycete rewires the metabolome of a marine bloom-forming diatom, thereby promoting infection success.